Langerhan’s Cell Histiocystosis - a case report - Khanal, R P; Basnet, S B; Neopane, A; Sharma, A P; Shah, K (Medical Journal of Shree Birendra Hospital, 2006)
Langerhan's Cell Histiocystosis - a case report Diagnostic challenge in a 21/2 years age girl: A cliniceo-radio-pathological correlation